Ganoderma lucidum Polysaccharide Enhanced the Antitumor Effects of 5-Fluorouracil against Gastric Cancer through Its Upregulation of NKG2D/MICA - Xi Yang; Rui Zhang; Jing Yao; Chen Xi; Shuzhang Du (International Journal of Polymer Science)
5-Fluorouracil (5-Fu) is one of the frequently used first-line cytotoxic drugs for chemotherapy against gastric cancer. Chemotherapy and immunotherapy are currently the main methods for treating gastric cancer. Immunotherapy can enhance the antitumor effect of chemotherapy drugs at the same time reducing its toxicity. The combination of these two therapies to treat cancer has become a mainstay and has received increasing attention in clinical practice. Ganoderma lucidum polysaccharide (GLP) is isolated from the Ganoderma lucidum fruiting body. Studies have shown that GLP has antitumor effects, where GLP does not directly kill tumors, rather exerting its antitumor function by stimulating immune cells including natural killer (NK) cells and T cells. In this study, the antitumor effect of GLP combined with 5-Fu was studied in vivo. At the same time, the associated mechanism of GLP combined with 5-Fu in gastric cancer cell lines BGC823 and SGC7901 was investigated in vitro. The results showed that GLP could stimulate the killing effect of NK-92 cells on gastric cancer cell lines BGC823 and SGC7901 and synergistically enhance the toxic effects of NK-92 cells on gastric cancer cell lines BGC823 and SGC7901. Moreover, GLP could further promote the activity of NK-92 cells by activating the NK cell activating receptor NKG2D and its downstream DAP10/PI3K/ERK signaling pathway.